Simple Exercises at Home During Social Distancing to Avoid Covid-19 - Fauzi, Rizal Ahmad (Journal of Physical Education Health and Sport, 2020)
This study aims to examine several exercises that can be done at home during the Covid 19 pandemic or when practicing social distancing. Material and methods: This study implements descriptive methods to examine various possible exercises to do at home. The exercises discussed in this study are easy to do but full of benefits. In addition, these exercises also do not require special equipment available in gyms.Result: The kinds of exercises discussed in this article include: (1) cardiovascular exercises that aim to improve cardiovascular (heart and blood vessel) fitness and lungs’ respiratory capacity and (2) exercises to strengthen muscles and bones, which aim to promote bone and muscle strengths in order to facilitate us doing activities without any motion problems. Conclusion: there are at least thirteen types of exercises that can be adopted as home-based alternatives of exercises without partner or special equipment. As has been mentioned, these exercises are improving cardiovascular fitness and muscular strength. Doing medium-intensity exercises routinely will improve immune system.